Heartfelt Impact: A Descriptive Analysis of Ceftaroline-Containing Regimens in Endocarditis due to Methicillin-Resistant Staphylococcus aureus - Kaylee E. Caniff; Chloe Judd; Kristen Lucas; Sandra Goro; Caroline Orzol; Mirna Eshaya; Mohammed Al Musawa; Michael P. Veve; Michael J. Rybak (Infectious Diseases and Therapy)
Abstract Introduction Infective endocarditis (IE) due to methicillin-resistant Staphylococcus aureus (MRSA) is characterized by frequent treatment failure to first-line agents and high mortality, necessitating use of alternative management strategies. Ceftaroline fosamil (CPT) is a cephalosporin antibiotic with activity against MRSA but without regulatory approval for the indication of IE. This study describes clinical experience with CPT-based regimens utilized in MRSA-IE. Methods This is a retrospective, observational, descriptive analysis of patients from two major urban medical centers in Detroit, Michigan from 2011 to 2023. Included adult patients (≥ 18 years) had ≥ 1 positive blood culture for MRSA, met definitive clinical criteria for IE, and received CPT for ≥ 72 h. The primary outcome was treatment failure, defined as a composite of 30-day all-cause mortality from index culture or failure to improve or resolve infectious signs/symptoms after CPT initiation. Results Seventy patients were included. The median (interquartile range [IQR]) age was 51 (34–63) years and 45.7% were male. Persons with injection drug use (PWID) made up 55.7% of the cohort and right-sided IE was the most prevalent subtype (50.0%). CPT was frequently employed second-line or later, often in combination with vancomycin (10.0%) or daptomycin (72.9%). Overall, 31.4% experienced treatment failure and 30-day all-cause mortality occurred in 15.7%. Conclusions These findings illustrate the challenges posed by MRSA-IE, including frequent treatment failures, and highlight the utilization of CPT as salvage therapy. Comparative studies are needed to more clearly define its role in MRSA-IE.